Boreal forest fire CO and CH4emission factors derived from tower observations in Alaska during the extreme fire season of 2015 - Wiggins, E.B.; Andrews, A.; Sweeney, C.; Miller, J.B.; Miller, C.E.; Veraverbeke, S.; Commane, R.; Wofsy, S.; Henderson, J.M.; Randerson, J.T. (Atmospheric Chemistry and Physics, 2021)
© Author(s) 2021.Recent increases in boreal forest burned area, which have been linked with climate warming, highlight the need to better understand the composition of wildfire emissions and their atmospheric impacts. Here we quantified emission factors for CO and CH4 from a massive regional fire complex in interior Alaska during the summer of 2015 using continuous high-resolution trace gas observations from the Carbon in Arctic Reservoirs Vulnerability Experiment (CRV) tower in Fox, Alaska. Averaged over the 2015 fire season, the mean CO=CO2 emission ratio was 0.142-0.051, and the mean CO emission factor was 127-40 g kg-1 dry biomass burned. The CO=CO2 emission ratio was about 39% higher than the mean of previous estimates derived from aircraft sampling of wildfires from boreal North America. The mean CH4 =CO2 emission ratio was 0.010-0.004, and the CH4 emission factor was 5.3-1.8 g kg-1 dry biomass burned, which are consistent with the mean of previous reports. CO and CH4 emission ratios varied in synchrony, with higher CH4 emission factors observed during periods with lower modified combustion efficiency (MCE). By coupling a fire emissions inventory with an atmospheric model, we identified at least 34 individual fires that contributed to trace gas variations measured at the CRV tower, representing a sample size that is nearly the same as the total number of boreal fires measured in all previous field campaigns. The model also indicated that typical mean transit times between trace gas emission within a fire perimeter and tower measurement were 1-3 d, indicating that the time series sampled combustion across day and night burning phases. The high CO emission ratio estimates reported here provide evidence for a prominent role of smoldering combustion and illustrate the importance of continuously sampling fires across timevarying environmental conditions that are representative of a fire season.